Valores humanos nas organizações: relação com a síndrome de Burnout e o engajamento laboral - Coelho, Gabriel Lins de Holanda (2014)
For many decades the research in organizations focus on the negative aspects caused on workers, with the burnout syndrome as the main exponent. In recent years, with the expansion of Positive Psychology, the interest in the positive aspects increased and resulted in the study of work engagement, considered the antithesis of burnout and essential to maximizing the human material in organizations. However, to the implementation of an environment that is conducive to stimulate engagement, it is necessary to review the values inside the organization, in order to find out what should be prioritized and shared among employees. At first, we tried to observe how the instruments Maslach Burnout Inventory (MBI) and Utrecht Work Engagement Scale (UWES) behave in a Brazilian context. The second study aimed to observe the influence of human values in the work engagement and burnout. Thus, this work was divided in two studies. Participated in Study 1, 180 workers of different professions, with as average age of 36.9 years (sd = 11.9), mostly women (62.2%). A confirmatory factor analysis was used to observe the structure of the instruments. The results were significant for the MBI [χ²/g.l. = 2,19, GFI = .82, AGFI = .77, CFI = .81 and RMSEA = .08 (IC90% = .071-.092)] and the UWES [χ² /gl = 3,02, GFI = .82, AGFI = .76, CFI = .88 and RMSEA = .10 (IC90% = .094-.119)]. Participated in study 2, 345 teachers, with an average age of 36.4 (sd = 10.33), mostly female (73,9%). Pearsons r correlations, analyses of mediation and moderation were performed. It was observed correlations of values with almost all factors of engagement and burnout. We tried to observe the effects of values on the engagement, being mediated by burnout, getting significant results in the social orientation [λ = .14 (IC90% = .01/.29; p = .05)]. Subsequently, Subsequently, we tried to observe the influence of the interaction between social values and the factors of burnout on engagement, yielding no significant results (p > .05). We opted for the realization of a new moderation, using the interactive subfunction, because it has greater explanatory weight, and reduced professional efficacy, the only dimension of burnout with significant correlations with the values. The results were statistically significant [β = .16, t = 2.26, p < .05; R ² = .32, adjusted R ² = .32, ΔR ² = .01, p < .05; F (1, 341) = 5.128, p < .05]. Through the simple slopes, we found that this relationship makes more sense at high levels (simple slope = .23, t = 3.04, p < .001) and average (simple slope = .12, t = 2.68 , p < .05) reduced professional efficacy. The results suggest the importance of interactive subfunction and social relations for the creation and maintenance of an environment with greater engagement from the employees, as evidenced in the JD-R model, used to explain the phenomenon. In short, it emphasizes the importance of the study of these constructs and trust that the objectives of this dissertation were achieved, contributing to the studies about human values and well-being in the workplace.